Fine mapping and cloning of the major seed protein quantitative trait loci on soybean chromosome 20. (10th February 2022) - Fliege, Christina E.; Ward, Russell A.; Vogel, Pamela; Nguyen, Hanh; Quach, Truyen; Guo, Ming; Viana, João Paulo Gomes; dos Santos, Lucas Borges; Specht, James E.; Clemente, Tom E.; Hudson, Matthew E.; Diers, Brian W.
Significance Statement: Soybean is the most important source of protein meal worldwide and the quantitative trait loci (QTL) cqSeed protein‐003 on chromosome 20 exerts the greatest additive effect of any protein QTL mapped in the crop. Through genetic mapping and candidate gene downregulation, we identified that an insertion/deletion variant in Glyma.20G85100 is the likely gene that underlies this important QTL. SUMMARY: Soybean [ Glycine max (L.) Merr.] is a unique crop species because it has high levels of both protein and oil in its seed. Of the many quantitative trait loci (QTL) controlling soybean seed protein content, alleles of the cqSeed protein‐003 QTL on chromosome 20 exert the greatest additive effect. The high‐protein allele exists in both cultivated and wild soybean ( Glycine soja Siebold & Zucc.) germplasm. Our objective was to fine map this QTL to enable positional‐based cloning of its underlying causative gene(s). Fine mapping was achieved by developing and testing a series of populations in which the chromosomal region surrounding the segregating high‐ versus low‐protein alleles was gradually narrowed, using marker‐based detection of recombinant events. The resultant 77.8 kb interval was directly sequenced from a G. soja source and compared with the reference genome to identify structural and sequence polymorphisms. An insertion/deletion variant detected in Glyma.20G85100 was found to have near‐perfect +/− concordance with high/low‐protein allele genotypes inferred for this QTL in parents of published mapping populations. The indel structure was concordant with an evolutionarily recent insertion of a TIR transposon into the gene in the low‐protein lineage. Seed protein was significantly greater in soybean expressing an RNAi hairpin downregulation element in two independent events relative to control null segregant lineages. We conclude that a transposon insertion within the CCT domain protein encoded by the Glyma.20G85100 gene accounts for the high/low seed protein alleles of the cqSeed protein‐003 QTL.